An overlooked cause in a patient with recurrent ischemic stroke: A case report. Issue 13 (March 2018) - Yang, Xunzhe; Liu, Mingsheng; Zhu, Yicheng; Zhang, Xiaobo; Gao, Shan; Ni, Jun
Abstract: Rationale: The majority of ischemic strokes are due to cardioembolism, large vessel atherothromboembolism, small vessel occlusive disease, or other unusual mechanisms. In most clinical settings, many strokes without a well-defined etiology requires a thorough diagnostic evaluation, otherwise the underlying cause might be easily overlooked. Here we report on the rare cause of a patient with recurrent stroke. Patient concerns: A 50-year-old female patient had a 4-year history of recurrent acute onset of neurological deficits. Diagnoses: Contrast transcranial Doppler ultrasound detected a typical "curtain" appearance of microbubbles, indicative of a right-to-left shunt. Computed tomography pulmonary angiogram was then initiated and a pulmonary arteriovenous malformation (PAVM) in the left lower lobe was found. Interventions: The patient underwent percutaneous closure of PAVM. Afterward, warfarin was commenced because of the high risk of further thromboembolic complications in the following weeks to months. Post-treatment computed tomography pulmonary angiogram (CTPA) demonstrated successful closure of PAVM. No microbubble signals were detected on post-treatment contrast transcranial Doppler ultrasound (TCD) study. Outcomes: The patient suffered no further embolic events during 3-year follow-up. No recanalization or new PAVMs were detected on CT scan. Lessons: Neurological PAVM-associated risks are common but remain poorly recognized. A strategic protocol is imperative in searching for the etiologies of cryptogenic stroke.